The Effect of Lemon aromatherapy on nausea and vomiting of pregnancy: A randomized clinical trial - Fahimeh Ezzati Arasteh; Fatemeh Shobeiri; Bayan Mafakheri; Younes Mohamadi; Parisa Parsa (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Nausea and vomiting are common complaints of women in the first half of the pregnancy. Nausea and vomiting of pregnancy significantly affect the quality of life of pregnant women. This study was performed with aim to evaluate the effect of lemon aromatherapy on nausea and vomiting of pregnancy. Methods: This double-blind clinical trial was performed on 88 pregnant women with nausea and vomiting referred to the health centers of Hamadan in 2017. The research tools was demographic questionnaire and pregnancy-unique quantification of emesis and nausea -24 questionnaire. The subjects were randomly divided into two groups of 44 women (lemon and placebo) and received lemon essence and placebo (distilled water) for four days. The severity of nausea and vomiting before and after the study were assessed. Data were analyzed by SPSS software (version 21) and Chi-square, independent t-test and Repeated Measures analysis. P Results: The groups were homogeneous for demographic information and pregnancy characteristics. After the aromatherapy intervention, the mean total score of nausea and vomiting decreased in the two groups of test and control, but in the experimental group, the mean score of nausea and vomiting significantly decreased over time compared to the control group (P = 0.007). Conclusion: The lemon essence is effective in reducing the nausea and vomiting of pregnant women, and it can be used as an effective and safe intervention in reducing nausea and vomiting in pregnant women.